Pemodelan dan Evaluasi Proses Bisnis menggunakan Quality Evaluation Framework (QEF) (Studi Kasus : Bidang Jaringan TIK dan Aplikasi KOMINFO Batu) - Agung Sudarmawan; Diah Priharsari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The Batu City Communication and Information Service is a new agency established in 2017. Currently, the Communication and Information Service has 4 fields, one of which is the field of ICT Infrastructure Network and Application. At a new age, the Communication and Information Service still has to make many improvements. One of them is in terms of business processes. To make improvements, an evaluation must be carried out first to find out the location of the shortcomings. To conduct the evaluation, the methods that the author will use are the Quality Evaluation Framework (QEF) method and 5 Whys Analysis. QEF is a suitable method to evaluate this study. Meanwhile, 5 Whys Analysis is a method introduced and used by toyota corporations to conduct an in-depth analysis of the systems they have. There are 8 business processes evaluated in this study. Of the 8 business processes evaluated, there are 12 quality factors written in Q1 to Q12. Of the 12 quality factors tested, there are 2 quality factors that have values that are not in accordance with the target.